2017
DOI: 10.3390/ijms18081758
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of Albumin Induces Matrix Metalloproteinase-9 by Activating the ERK Signaling Pathway in Renal Tubule Epithelial Cells

Abstract: Matrix metalloproteinase-9 (MMP-9) is dysregulated in chronic kidney diseases including diabetic nephropathy. This study was performed to examine the expression of MMP-9 in renal tubule epithelial cells (TECs) under diabetic conditions and its regulatory mechanisms. We characterized MMP-9 protein in diabetic animals and primary cultured rat TECs exposed to exogenous albumin and high glucose. We also used specific inhibitors to determine if internalization of albumin and/or extracellular signal-regulated kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
2
7
0
2
Order By: Relevance
“…We verified the mRNA levels of KIM-1, OPN, MCP-1/CCL2, and fibronectin-1 by real-time PCR and showed that KIM-1 was the most highly upregulated in diseased kidneys. These findings are in agreement with our previous reports showing that KIM-1, MCP-1, and OPN were upregulated in the kidneys of diabetic ZD rats [11,13,23].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We verified the mRNA levels of KIM-1, OPN, MCP-1/CCL2, and fibronectin-1 by real-time PCR and showed that KIM-1 was the most highly upregulated in diseased kidneys. These findings are in agreement with our previous reports showing that KIM-1, MCP-1, and OPN were upregulated in the kidneys of diabetic ZD rats [11,13,23].…”
Section: Discussionsupporting
confidence: 94%
“…KIM-1 upregulation has been shown to correlate with damage to the proximal tubule in both acute and chronic kidney diseases [18,19,20,21,22]. We have previously reported an induction of KIM-1 in proximal tubules of diabetic ZD rats [11,13,23]. Here, we expanded our study to examine the relationship between KIM-1 expression and lipid accumulation in renal tubules of ZO and ZD kidneys.…”
Section: Resultsmentioning
confidence: 91%
“…In accordance with previous reports, gossypin was reported to decrease oxidative stress markers and exerted a protective action in different models of the liver ( The MMPs, an important family of inflammatory enzymes, are sets of structurally associated proteins that are tangled in the extracellular matrix, inducing remodeling of several physiological and pathological circumstances (Cavdar et al, 2017). MMP-9 is one of the MMPs family locally secreted in response to renal pathological settings and may be involved in the initiation and severity of inflammatory kidney disorders (Chen et al, 2017). Furthermore, it was proved that elevated levels of MMP-9 were linked to tubular epithelial/mesenchyme alteration in vitro (Strutz et al, 2002).…”
Section: Discussionmentioning
confidence: 79%
“…According to previous studies, CS acts as a potent inducer for ERK phosphorylation, leading to the production of proinflammatory cytokines as well as MMPs [ 28 ]. In various studies, the activation of ERK signaling has been shown to induce MMP-9 expression, which is abolished in the presence of an ERK inhibitor [ 29 , 30 , 31 ]. In particular, Su et al [ 32 ] reported that DADS caused the suppression of the ERK/Fra-1 pathway, resulting in the downregulation of MMP-9 expression.…”
Section: Discussionmentioning
confidence: 99%